2019
DOI: 10.3389/fchem.2019.00453
|View full text |Cite
|
Sign up to set email alerts
|

Pd-Shaped Nanoparticles Modified by Gold ad-Atoms: Effects on Surface Structure and Activity Toward Glucose Electrooxidation

Abstract: Palladium nanoparticles (Pd-NPs) with controlled distributions of sizes and shapes (nanospheres–Pd-NS-, nanocubes -Pd-NC-, and nanooctahedrons -Pd-NO-) are synthesized by wet chemistry methods and characterized by TEM/HRTEM. The surfaces of Pd-NPs are modified by spontaneous adsorption of gold and characterized by cyclic voltammetry in acidic medium. It is shown that the modification of Pd-NPs by dipping in HAuCl 4 solutions of different concentrations allows controlling the surface cove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 45 publications
(56 reference statements)
0
5
0
Order By: Relevance
“…They can be also gained from glucose electro-oxidation, identifying and quantifying by HPLC. [70,71] As far as we know, it can be clearly found that the real catalytic active phase for glucose oxidation reaction (GOR) was metal oxidized species.…”
Section: Her and Glucose Oxidation Reactionmentioning
confidence: 99%
“…They can be also gained from glucose electro-oxidation, identifying and quantifying by HPLC. [70,71] As far as we know, it can be clearly found that the real catalytic active phase for glucose oxidation reaction (GOR) was metal oxidized species.…”
Section: Her and Glucose Oxidation Reactionmentioning
confidence: 99%
“…The coulombic charges in the reduction peaks allow determining the surface percentage of each structure and then determining the whole surface composition [25,27,41]. The surface of the Pd 3 Au 7 /C catalyst exhibits non-alloyed Au islands (56% of the surface) and two PdAu alloys with Pd/Au atomic compositions of 6/4 (36% of the surface) and 8/2 (8% of the surface) leading to a global surface composition of 28 at% Pd and 72 at% Au close to the bulk nominal one (30 at% Pd and 70 at% Au).…”
Section: Physicochemical Characterization Of Catalystsmentioning
confidence: 99%
“…Achieving a continuous process with good selectivity and specificity requires one to investigate the stability of the products obtained from glucose toward oxidation. At the positive electrode, electrooxidation of d -glucose to produce gluconic acid on various catalysts has been widely discussed. Some authors investigated the effect of surface orientation on the catalyst activity for glucose oxidation. It appeared that (100) surface domains were the most active ones for Au and Pd, whereas Pt(111) surface domains led to higher activity toward glucose oxidation. In comparison, few studies were carried out on gluconic acid oxidation. , Furthermore, as crossover of sorbitol (produced at the negative electrode) through the membrane cannot be excluded, its oxidation in the anode conditions has to be investigated equally. , …”
Section: Introductionmentioning
confidence: 99%